The mechanism of kaempferol induced apoptosis and inhibited proliferation in human cervical cancer SiHa cell: From macro to nano. Issue 6 (18th February 2016) - Tu, Lv‐Ying; Bai, Hai‐Hua; Cai, Ji‐Ye; Deng, Sui‐Ping
Summary: Kaempferol has been identified as a potential cancer therapeutic agent by an increasing amount of evidences. However, the changes in the topography of cell membrane induced by kaempferol at subcellular‐ or nanometer‐level were still unclear. In this work, the topographical changes of cytomembrane in human cervical cancer cell (SiHa) induced by kaempferol, as well as the role of kaempferol in apoptosis induction and its possible mechanisms, were investigated. At the macro level, MTT assays showed that kaempferol inhibited the proliferation of SiHa cells in a time‐ and dose‐dependent manner. Flow cytometry analysis demonstrated that kaempferol could induce SiHa cell apoptosis, mitochondrial membrane potential disruption, and intracellular free calcium elevation. At the micro level, fluorescence imaging by laser scanning confocal microscopy (LSCM) indicated that kaempferol could also destroy the networks of microtubules. Using high resolution atomic force microscopy (AFM), we determined the precise changes of cellular membrane induced by kaempferol at subcellular or nanometer level. The spindle‐shaped SiHa cells shrank after kaempferol treatment, with significantly increased cell surface roughness. These data showed structural characterizations of cellular topography in kaempferol‐induced SiHa cell apoptosis and might provide novel integrated information from macro to nano level to assess the impact of kaempferol on cancer cells, which might be important for the understanding of the anti‐cancer mechanisms of drugs. SCANNING 38:644–653, 2016. © 2016 Wiley Periodicals, Inc.